Main Determinants of Georgia's Transit Function Development - Irakli Danelia (European Scientific Journal, ESJ, 2017)
Due to the strategically important geographical location, Georgia has a key transit function throughout the Caucasus and beyond between Europe and Asia, but unfortunately transit potential of the country is used only partially. Nowadays, prospects and problems of the transit function for small country with very limited resources such as Georgia are vital issues for the country’s economy. Because of this, the purpous of the study is to identify the major determinants that play a crucial role in the development of transit function of the country. based on practical and theoretical significance of the research we used systemic, historical and logical generalization methods of research in the performance of the work, scientific abstraction, analysis and synthesis methods are also used.